2002
DOI: 10.1002/tera.10082
|View full text |Cite
|
Sign up to set email alerts
|

PBX, MEIS, and IGF‐I are potential mediators of retinoic acid‐induced proximodistal limb reduction defects

Abstract: Because both PBX and MEIS (and their orthologs) are believed to be involved in the control of proximodistal axis formation in mouse and fly limbs and IGFs in the development of limbs, we suggest that increases in PBX, MEIS and IGF-1 mRNA levels may contribute to proximodistal limb reduction defects caused by teratogenic doses of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 49 publications
4
38
1
Order By: Relevance
“…Our findings are consistent with previous studies demonstrating that Meis2 expression in the proximal limb mesoderm is reduced when RA receptor antagonists or RA synthesis inhibitors are introduced into chick limb buds (6) and that Meis2 expression is increased following a teratogenic dose of RA (6,20). We further demonstrate that expression of Tbx5 and Meis2 is observed in Raldh2 Ϫ/Ϫ forelimb buds rescued by maternal RA treatment limited to E8 during limb field establishment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are consistent with previous studies demonstrating that Meis2 expression in the proximal limb mesoderm is reduced when RA receptor antagonists or RA synthesis inhibitors are introduced into chick limb buds (6) and that Meis2 expression is increased following a teratogenic dose of RA (6,20). We further demonstrate that expression of Tbx5 and Meis2 is observed in Raldh2 Ϫ/Ϫ forelimb buds rescued by maternal RA treatment limited to E8 during limb field establishment.…”
Section: Discussionsupporting
confidence: 92%
“…By using inhibitors of RA synthesis or RA receptor antagonists, RA was reported to be required for Meis homeobox gene expression, which is normally limited to the proximal region of limb buds where it helps control proximodistal axis formation (6). Also, excess RA induces proximodistal limb reductions, and this is associated with an increase in Meis expression (20). It has been hypothesized that proximodistal limb expression of Meis genes is regulated by opposing signals, i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding limb development, we confirmed that meis1/2 are expressed along the lateral plate mesoderm before limb outgrowth, but are down-regulated in an ectodermic/mesodermic area near the distalmost limb bud at around stages HH18-HH19, as previously reported for both chicken and mouse (Cecconi et al, 1997;Oulad-Abdelghani et al, 1997;Capdevila et al, 1999;Mercader et al, 1999;Coy and Borycki, 2010). This suggests they have a role in proximodistal axis specification in an RA-dependent way (Mercader et al, 2000(Mercader et al, , 2005Qin et al, 2002;Yashiro et al, 2004). In contrast, meis2 expression is not observed in the limb rudiment of zebrafish embryos (Biemar et al, 2001;Zerucha and Prince, 2001).…”
Section: Meis Gene Expression During Sensory Organ Developmentsupporting
confidence: 88%
“…Expression of Meis is also associated with hematopoiesis and angiogenesis (Hisa et al, 2004;Azcoitia et al, 2005), and to morphogenesis and specification of the developing eye (Hisa et al, 2004;Bumsted-O'Brien et al, 2007), the olfactory system (Hisa et al, 2004;Oulad-Abdelghani et al, 1997;Toresson et al, 2000), and the developing inner ear (Oulad-Abdelghani et al, 1997;Zerucha and Prince, 2001;Hisa et al, 2004;Sá nchez-Guardado et al, 2011). Furthermore, Meis genes control cell fate specification along the proximal-distal axis of the developing vertebrate limb buds and Drosophila legs (Capdevila et al, 1999;Mercader et al, 1999Mercader et al, , 2000Wu and Cohen, 1999;Qin et al, 2002;Yashiro et al, 2004). In addition, several studies have provided evidence that Meis expression influences early patterning in several organs, such as liver, lungs, and kidney, among others (Hisa et al, 2004).…”
Section: Introductionmentioning
confidence: 99%